A new miniature species of geophilomorph centipede from the Ecuadorian Amazon rainforest (Chilopoda: Geophilomorpha: Ballophilidae). (4th May 2018) - Pereira, Luis Alberto
ABSTRACT: A new miniature species of geophilomorph centipede, Ityphilus grismadoi sp. nov. (Chilopoda: Geophilomorpha: Ballophilidae) is fully described and illustrated on the basis of specimens collected in Yasuní Scientific Station and Jatun Sacha Biological Station, both located in the Ecuadorian Amazon. The new species is characterized by having the internal edge of the forcipular tarsungulum completely smooth, this trait being shared by six other Neotropical members of the genus Ityphilus Cook, 1899; and another species ( I. cifuentesi Cupul Magaña, 2014) from the transition area between the Neotropical and Nearctic regions. Ityphilus grismadoi sp. nov. is distinguished from these seven species by the low number of leg-bearing segments (37, 39), and the very small body size (7–9 mm in length) and for a confident identification it is compared in detail with those having a roughly similar range of leg-bearing segments. This is the first record of the genus Ityphilus from Ecuador and the second report of a ballophilid centipede from the country (the other represented by Zygethmus pantenus Chamberlin, 1957). A key to the Neotropical members of Ityphilus with forcipular tarsungulum smooth (including I. cifuentesi ) is also given. http://zoobank.org/urn:lsid:zoobank.org:pub:32F77890-9DC5-47AC-A794-29C4437C3B93 http://zoobank.org/urn:lsid:zoobank.org:act:3EB64970-F159-4C6E-B9FF-AF9D09128553